2021
DOI: 10.21203/rs.3.rs-283734/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of LncRNA MALAT-1 and MiRNA-9 in Psoriasis

Abstract: Background: Psoriasis is a chronic skin disorder manifested by recurrent episodes of scaly, red, itchy skin patches that occur within apparently normal skin. Objectives: This study was performed to detect the expression of serum and tissue (lesion and non-lesion) LncRNA MALAT-1 and MiRNA-9 that might be used as biomarkers for psoriasis. Methods: 100 subjects were included in this study, 60 psoriatic patients as well as 40 controls, blood samples were taken from all subjects, 4 mm punch biopsy was taken from le… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Psoriasis is a skin disease that can be stimulated by many environmental factors, controlled by polygenes, such as MEG3 and MALAT1 [17, 18], and mediated by immune mechanisms. According to research findings, XIST plays an important role in a variety of diseases through regulating the inflammatory response [17, 19].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Psoriasis is a skin disease that can be stimulated by many environmental factors, controlled by polygenes, such as MEG3 and MALAT1 [17, 18], and mediated by immune mechanisms. According to research findings, XIST plays an important role in a variety of diseases through regulating the inflammatory response [17, 19].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Psoriasis is chronic common autoimmune disease of the skin which affects most populations 2 . PD‐1 and ANG‐2 are two proteins that are reported to have a potential role in regulating the immune system's response to the cells of the human body as general 4,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is considered as a chronic, recurrent disease that is related to the activation of T cells, including T helper 1 cells and 17 (Th1 and Th17). The T cells promote cutaneous inflammation and keratinocyte hyper proliferation 1,2 . As well the dysfunctional regulatory T (Treg) cells disrupt immune tolerance which in return leads to the induction of autoimmunity and auto‐inflammatory diseases like psoriasis 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastasis-associated lung adenocarcinoma transcript-1 (MALAT1) is a kind of LncRNA that acts as a crucial part in regulating the process of Lupus erythematosus (SLE) [10,11]. Some researchers have shown that MALAT1 is positively correlated to the area severity of psoriasis patients [12]. MALAT1 may promote the progression of psoriasis via miR-330-5p/S100A7 axis [13].…”
Section: Introductionmentioning
confidence: 99%